40.3 TARGETING NMDAR HYPOFUNCTION DURING EARLY DEVELOPMENT FOR THE PREVENTION OF SCHIZOPHRENIA PHENOTYPES IN ADULTHOOD IN THE MAM MODEL. (9th April 2019) - Gao, Wen-Jun; Xing, Bo; Li, Meng-lin; Gulchina, Yelena
Abstract: Background: Glutamate hypofunction has been a prominent hypothesis in the understanding of schizophrenia (SCZ) pathology. Particularly, the N-methyl-D-aspartate receptor (NMDAR), a major glutamate receptor subtype, demonstrates alterations in post-mortem studies, and prefrontal glutamatergic hypofunction is speculated to underlie cognitive deficits that remain untreatable. However, little attention has been given to the NMDAR system in the developing prefrontal cortex (PFC) in models of SCZ. Because cognitive impairments emerge prior to psychosis onset, we investigated synaptic function, focusing on NMDARs, during the early stage of development in the methylazoxymethanol acetate (MAM) model for SCZ. Methods: MAM model: At E17, pregnant rats were injected with 25 mg/kg MAM or saline vehicle. Western blotting: PFC was extracted from P21 (juvenile) or P60 (adult) saline or MAM-exposed animals. Whole-cell patch clamp electrophysiology. ChiP-qPCR: PFC tissue from juvenile MAM and saline rats was sheared and separately immunoprecipitated with REST and H3K27me3 antibodies. qPCR was conducted in triplicate with primers for the Grin1, Grin2a, and Grin2b promoter regions. Drugs and behavioral tests: Juvenile treatment with mGluR2 agonist/mGluR3 antagonist LY395756 (subchronic, 0.3 mg/kg, i.p., once daily for 5 days; Cross-maze); mGluR2/3 agonist LY379268 (0.1, 0.3, 1mg/kg, i.p., once daily for 5 days; Morris water maze, T maze, and locomotor activity) from P21 to P25; GSK3b inhibitor SB216763 (2 mg/kg/day or vehicle, once daily for 8 days; T maze) from P21 to P28. Results: We found that the levels of synaptic NR2B protein are significantly decreased in juvenile MAM animals, and the function of NMDARs is substantially compromised as reflected in decreased NMDA-EPSCs. The protein loss was in juvenility correlated with an aberrant increase in the enrichment of the epigenetic transcriptional repressor REST and the repressive histone marker H3K27me3 at the Grin2b promoter, as assayed by ChIP-qPCR. In adulthood, MAM animals exhibited PFC-dependent learning and memory deficits. Both prefrontal NMDAR hypofunction and cognitive deficits were prevented by treatment with either mGluR2/3 modulators (mGluR2 agonist/mGluR3 antagonist LY395756t and mGluR2/3 agonist LY379268) or GSK3b inhibitor in the juvenile, but not adult rats. LY395756 prevented NMDA dysfunction, learning deficits, and cognitive flexibility. Both LY379268 and GSK3β inhibitor SB216763 also prevented NMDAR dysfunction and learning and memory deficits, as well as dendritic spine loss. We also found that the preventive effects of 0.3 mg/kg LY379268 were mediated by improving GluN2B-NMDAR function via inhibiting GSK3β. However, targeting GSK3β in juveniles with SB216763 also altered dendritic spine morphology in control animals, whereas LY379268 exhibited no lasting effects on prefrontal neuronal excitability and excitatory synaptic transmission even 10 weeks after treatment in juvenile. Conclusions: Our work confirmed that NMDAR hypofunction is a feature of early postnatal development, with epigenetic hyper-repression of the Grin2b promoter being a contributing factor. The selective loss of NR2B protein and subsequent synaptic dysfunction weakens the PFC function during development and may underlie early cognitive impairments in SCZ models and patients. The latter is supported by the efficacy of glutamatergic modulators to prevent both prefrontal NMDAR hypofunction and cognitive deficits, highlighting the importance of targeting glutamatergic dysfunction as a potential early intervention for SCZ.